Delayed onset of breastfeeding: what is stopping us? - Gadhavi, Ketan; Deo, Ruta (International Journal of Contemporary Pediatrics, 2020)
Background: Breastfeeding is the best meal for a new born child. Various initiatives are in place for early initiation of breastfeeding. The effectiveness of these interventions is put to question when a large number of neonates fail to receive breast milk soon after birth. This study analyses the parameters likely to affect the time of onset of breastfeeding and evaluate the scope for interventions. It is important to assess the factors affecting initiation of breastfeeding, determine the relationship of these factors with the time of initiation and to analyse if counselling by health care workers has any benefit on outcome. Methods: This is a hospital based cross sectional observational study in 200 lactating mothers from a pre-designed questionnaire. Main outcome measure- early onset (<1 hour of birth) of breastfeeding. Results: Only 55% neonates included in this study were breastfed within the first 30 minutes. Positive influence for early initiation of breastfeeding was found with non primi mothers aged more than 26 years, with secondary or higher education, who had vaginal birth with institutional delivery. Early oral intake of mother with professional women living in joint family started early breastfeeding. Use of pre lacteal feeds delayed the onset of breastfeeding. Infants fed earlier were males, weight >2.2 kg. Women counselled by health care workers fed their babies earlier. Conclusions: This study surmises that pre lacteal feeds should be discouraged and active health care workers’ participation should be encouraged for early breastfeeding. Breastfeeding should be initiated as soon as possible for healthy neonatal outcome.